Probing flecainide block of INa using human pluripotent stem cell-derived ventricular cardiomyocytes adapted to automated patch-clamping and 2D monolayers. (15th September 2018) - Geng, Lin; Kong, Chi-Wing; Wong, Andy O.T.; Shum, Angie Man-Yee; Chow, Maggie Z.Y.; Che, Hui; Zhang, Chenzi; Yau, Ka-Long; Chan, Camie W.; Keung, Wendy; Li, Ronald A.
Highlights: Well-characterized single hPSC-VCMs could be readily adapted for automated current- and voltage-clamping assays. Multi-cellular electrophysiological assessments with hvCMLs can predict drug-induced reentrant arrhythmias. A combinatorial approach using single-cell EP and hvCMLs is needed to comprehensively assess drug-induced arrhythmogenicity. Abstract: Human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) are emerging tools for applications such as drug discovery and screening for pro-arrhythmogenicity and cardiotoxicity as leading causes for drug attrition. Understanding the electrophysiology (EP) of hPSC-CMs is essential but conventional manual patch-clamping is highly laborious and low-throughput. Here we adapted hPSC-CMs derived from two human embryonic stem cell (hESC) lines, HES2 and H7, for a 16-channel automated planar-recording approach for single-cell EP characterization. Automated current- and voltage-clamping, with an overall success rate of 55.0 ± 11.3%, indicated that 90% of hPSC-CMs displayed ventricular-like action potential (AP) and the ventricular cardiomyocytes (VCMs) derived from the two hESC lines expressed similar levels of INa, ICaL, Ikr and If and similarly lacked Ito and IK1 . These well-characterized hPSC-VCMs could also be readily adapted for automated assays of pro-arrhythmic drug screening. As an example, we showed that flecainide (FLE) induced INa blockade, leftward steady-state inactivation shift, slowed recovery from inactivation in our hPSC-VCMs. Since single-cell EP assay is insufficient to predict drug-induced reentrant arrhythmias, hPSC-VCMs were further reassembled into 2D human ventricular cardiac monolayers (hvCMLs) for multi-cellular electrophysiological assessments. Indeed, FLE significantly slowed the conduction velocity while causing AP prolongation. Our RNA-seq data suggested that cell-cell interaction enhanced the maturity of hPSC-VCMs. Taken collectively, a combinatorial approach using single-cell EP and hvCMLs is needed to comprehensively assess drug-induced arrhythmogenicity.